Faktor – Faktor yang Mempengaruhi Minat Belanja Mahasiswa pada Aplikasi Shopee - Abdul Jalal; Mirza Ayunda Pratiwi (Bahtera Inovasi, 2023)
In this technological age, many people choose to buy and sell through online shopping applications. Students in the class of 2023 belong to generation Z, which is more interested in shopping through apps than previous generations. Shopee is one of the marketplaces that Gen Z finds appealing. As a result, the goal of this study is to determine what factors influence student shopping interest in the Shopee application. As a sample, students majoring in Management from the class of 2021 are used in this study. The data was analyzed using descriptive statistics and multiple regression. According to the findings of this study, the discount discount and ease of shopping variables had a significant impact on student shopping interest in the Shopee application. Then, the discount variable and the convenience of shopping simultaneously influence student shopping interest in the Shopee application.